Stab injury of the superior mesenteric artery with life threatening bleeding - endovascular treatment with an unusual technique - Demirel, Serdar; Winter, C.; Rapprich, B.; Weigand, H.; Gamstätter, G. (Vasa, 2010)
Endovascular microcoil embolization of the superior mesenteric artery (SMA) main trunk is not currently employed as a treatment for penetrating injury to the SMA in hemodynamically instable patients. Immediate laparotomy is the initial gold standard therapy. We report a case of successful SMA microcoil embolization with preservation of mesenteric perfusion by an unusual endovascular technique.
Online veröffentlicht: January 07, 2013
Gesehen am 05.01.2024